CTCF mediates insulator function at the CFTR locus - Blackledge, Neil P.; Carter, Emma J.; Evans, Joanne R.; Lawson, Victoria; Rowntree, Rebecca K.; Harris, Ann (Biochemical journal, 2007)
Regulatory elements that lie outside the basal promoter of a gene may be revealed by local changes in chromatin structure and histone modifications. The promoter of the CFTR (cystic fibrosis transmembrane conductance regulator) gene is not responsible for its complex pattern of expression. To identify important regulatory elements for CFTR we have previously mapped DHS (DNase I-hypersensitive sites) across 400 kb spanning the locus. Of particular interest were two DHS that flank the CFTR gene, upstream at −20.9 kb with respect to the translational start site, and downstream at +15.6 kb. In the present study we show that these two DHS possess enhancer-blocking activity and bind proteins that are characteristic of known insulator elements. The DHS core at −20.9 kb binds CTCF (CCCTC-binding factor) both in vitro and in vivo; however, the +15.6 kb core appears to bind other factors. Histone-modification analysis across the CFTR locus highlights structural differences between the −20.9 kb and +15.6 kb DHS, further suggesting that these two insulator elements may operate by distinct mechanisms. We propose that these two DHS mark the boundaries of the CFTR gene functional unit and establish a chromatin domain within which the complex profile of CFTR expression is maintained.